2018
DOI: 10.7554/elife.40664
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-dependent dynamics of the BK channel cytosolic gating ring are coupled to the membrane-embedded voltage sensor

Abstract: In humans, large conductance voltage- and calcium-dependent potassium (BK) channels are regulated allosterically by transmembrane voltage and intracellular Ca2+. Divalent cation binding sites reside within the gating ring formed by two Regulator of Conductance of Potassium (RCK) domains per subunit. Using patch-clamp fluorometry, we show that Ca2+ binding to the RCK1 domain triggers gating ring rearrangements that depend on transmembrane voltage. Because the gating ring is outside the electric field, this volt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 71 publications
2
25
0
Order By: Relevance
“…The voltage dependence of Ca 2+ -dependent gating ring rearrangements (Miranda et al, 2013; Miranda et al, 2018) and RCK1 site occupancy (Sweet and Cox, 2008; Savalli et al, 2012; Miranda et al, 2018) as well as the perturbation of VSD movements by Ca 2+ binding (Savalli et al, 2012) support the idea that the energetic interaction between both specialized sensors may be crucial for BK channel activation. The physical CTD-VSD interface has been suggested to provide the structure capable of mediating the crosstalk between these sensory modules and their synergy in activating the pore domain (Yang et al, 2007; Sun et al, 2013; Tao et al, 2017; Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 71%
“…The voltage dependence of Ca 2+ -dependent gating ring rearrangements (Miranda et al, 2013; Miranda et al, 2018) and RCK1 site occupancy (Sweet and Cox, 2008; Savalli et al, 2012; Miranda et al, 2018) as well as the perturbation of VSD movements by Ca 2+ binding (Savalli et al, 2012) support the idea that the energetic interaction between both specialized sensors may be crucial for BK channel activation. The physical CTD-VSD interface has been suggested to provide the structure capable of mediating the crosstalk between these sensory modules and their synergy in activating the pore domain (Yang et al, 2007; Sun et al, 2013; Tao et al, 2017; Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 71%
“…The αB Helix/VSD Interface is Required for Effective Voltage and Ca 2+ Activation of BK Channels. Functional studies have suggested that voltage and Ca 2+ sensors of BK channels interact, as summarized in the Introduction (6,13,15,28,30,40,41,43,44), and that the AC (N-lobe) region of the CTD is involved (25,51). Structural studies have identified a potential structural pathway to couple Ca 2+ sensors in the CTD with voltage sensors in the TMD (16,17,31).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also indications of some potential differences in activation pathways, as Ca 2+ binding is voltage dependent at the RCK1 Ca 2+ site, but not at the Ca 2+ bowl site (41), and strong correlation has been observed between VSD function and RCK1 conformational changes, but not between RCK2 and VSD function (44). Additional evidence for some possible differences in the RCK1 Ca 2+ site activation pathway and the Ca 2+ bowl activation pathway are our observations that disruption of the αB helix with L390P reduced the fractional contribution to Ca 2+ sensitivity from RCK1 Ca 2+ sites more than from Ca 2+ bowl sites ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In structure, the BK channels mainly consist of two subunits: pore-forming α subunit and auxiliary β subunit, which form a tetramer (Ge et al, 2014). The α subunit is composed of seven transmembrane domains (S0-S6) (Miranda et al, 2018), including extracellular N terminals, voltage-sensitive domains, and cytoplasmic C ends with calcium and other regulatory molecule binding sites. There are four subtypes of β subunits (β1-β4) (Bhattarai et al, 2014), and mainly β1 subunit is in vascular smooth muscle cells.…”
Section: Bk Channel Dysfunction In Diabetic Coronary Arterymentioning
confidence: 99%